Theory and practice of clinical trials in oncology and hematology - N. V. Zhukov (Онкогематология, 2016)
In the era of evidence-based medicine the main reason for the implementation of new treatment methods are the results of clinical trials. However, clinical trials is a separate area of knowledge, which is often little known to clinicians, that does not allow them to adequately interpret the results of studies. The article describes the basic principles for the conduct and interpretation of clinical trials in hematology and oncology.